SUICIDAL HANGING: A FIVE-YEAR ANALYSIS AT A TERTIARY HEALTH CENTER IN SOUTH INDIA - Chaudhari, Vinod Ashok; N, Ashok; Das, Siddhartha; Patil, Aruna Bholenath; Sahu, Swaroop Kumar (Journal of Forensic Medicine and Toxicology, 2024)
Suicide is a global burden, accounting for more than seven lakh deaths annually, with a range of one suicide every 40 seconds. India reports the highest number of suicides in the world. Hanging is the most common method, followed by poisoning and burns. Records from a tertiary centre in Southern India were examined retrospectively for the study between 2010 and 2014. We studied 147 cases of hanging out of 3996 autopsies conducted in our tertiary health centre. Data was collected from the police inquest and postmortem examination reports from 2010 to 2014. Males (55%) are more commonly affected than females (45%). Around 45% of cases occurred during the third decade of life. The present study reveals that a higher proportion of cases (54%) were reported from rural regions, with family problems being the most prevalent reason among both genders. The second most common reason was financial problems in males. The leading cause of hanging in adult females was found to be dowry harassment, while academic pressure was the primary cause in minor females. The vast majority of cases (94%) occurred within the victim’s residence, with the most commonly used material being saree (37%), followed by rope (27%). Approximately 74% of cases were completed, and 81% were typical hanging. In 64% of cases, the internal structures beneath the ligature mark were found to be intact. Duration of survival analysis conducted between rural and urban regions revealed that a significant proportion of cases that survived for < 24 hours belonged to rural regions.
Keywords: Hanging; Autopsy; Ligature Material; Rural; India; Neck